Moore–Gibson–Thompson Stability Model in a Two-Temperature Photonic Semiconductor Excited Medium Affected by Rotation and Initial Stress - Riadh Chteoui; Kh. Lotfy; M. A. Seddeek; A. El-Dali; W. S. Hassanin (Crystals, 2022)
In this paper, the two-temperature theory is used to examine a novel model that generalizes the Moore–Gibson–Thompson (MGT) effect according to two-dimensional electronic/thermoelastic deformation. The main equations for a semiconductor medium in the context of the impact of rotation are explained in terms of the impact of the initial hydrostatic stress at the free surface. The normal-mode approach is used to derive the precise formulae for the fundamental physical quantities (i.e., normal displacement, normal load stress, electronic diffusion (carrier density), dynamic and conductive temperature distribution) under the influence of the two-temperature coefficient. The comparison with the base state is performed using linear stability analysis. To make some comparisons based on the various values of thermal memories, the influence of a number of novel parameters is applied to each of our primary physical quantities, such as the rotation parameter and the initial stress. An example of the main fields’ perturbation is also obtained and graphically described.